Transformasi Arsitektur Tradisional ke Arsitektur Modern di Lingkungan Perkotaan - Farida Khoirun Nisa; Nia Zahra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The transformation of traditional architecture into modern architecture in urban environments reflects a shift in the values, functions, and aesthetics of buildings in response to the ever-growing needs of society. Traditional architecture that is strong with cultural elements and environmental adaptation now faces major challenges with the emergence of modern architecture that is more minimalist, efficient, and prioritizes technology. This study aims to examine how traditional architectural elements can be maintained and integrated into modern architectural designs in urban areas, especially in an effort to maintain cultural identity and answer the need for sustainable and environmentally friendly buildings. The transformation of traditional architecture into modern architecture in urban environments is a complex and interesting process. This change occurs in response to the development of the times and technology. Traditional architecture has important historical and cultural values, but with the presence of modern architecture, there are changes in the form, materials, and functions of buildings. With this transformation, there is a change in the order of the urban environment Modern buildings built around traditional buildings create an interesting contrast and reflect a blend of the past and the present. The transformation of traditional architecture into modern architecture in urban environments is a process that continues to develop and provides new colors in the world of architecture.